Pengaruh Bauran Pemasaran Jasa Terhadap Kepuasan Penumpang Kereta Api Serayu - Diah Laely Astuti (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2017)
Train is the passenger and goods transport services which can carry large loads over long distances or at close range, train travel is not affected by the weather so many people are choosing this mode of transportation. One types of train that Railways Serayu, which is a train route Pasar Senen-Purwokerto. There is a problem on trains serayu relating to hotchpotch marketing services and satisfaction passengers. This study aims to to see how hotchpotch marketing services, satisfaction passengers and influence hotchpotch marketing services to satisfaction train passengers serayu simultaneously and partial. This research using quantitative methods. This type of research is descriptive and causal, with questionnaire collection methods. Based on descriptive analysis, service marketing mix on Serayu train have a percentage of 76,25%, it is in good category. Passenger satisfaction has a percentage of 75,47%, it shows in the good category. The results of this research are the of marketing mix consisting of product, price, place, promotion, people, process, physical environment simultaneously significantly influence passenger satisfaction amounted to 84,8%, while the remaining 15,2% influenced by other variables not examined in this study. Variable product, price, place and promotion partially not significantly affect passenger satisfaction. Variables people, process, and partially physical environment significantly influence passenger satisfaction.